Category membership and category potential: The case of vague because - Martin Konvička (Lexis: Journal in English Lexicology)
I analyse the English causal connector because as used in the so-called because X constructions in terms of its word class membership. I show that three types of because can be distinguished based on syntactic criteria. Depending on the complement of the connector, because can be used as a conjunction, as a preposition, and as a member of a third category. I also show that prior to use, we can only talk about an abstract category potential of the connector, but not about its concrete category membership. It is only through the context of use that becomes category membership apparent. On a more general note, this means that linguistic categories should be understood as being emergent from language use, not essentialistically as existing before and being independent of language use.